Understanding Barriers to the Access to Healthcare and Rehabilitation Services: A Qualitative Study with Mothers or Female Caregivers of Children with a Disability in Indonesia - Gregorius Abanit Asa (MDPI AG, 2021)
Accessibility to healthcare and rehabilitation services for children with a disability (CWD) is essential to improving their health and wellbeing. However, access to the services, especially in many settings in developing countries with scarcity of resources, is still limited. As part of a qualitative study exploring impacts of caring for CWD on mothers or female caregivers and their coping strategies, this paper describes barriers for access to healthcare and rehabilitation services for CWD in Belu district, Indonesia. One-on-one, in-depth interviews were conducted with 22 mothers or female caregivers of CWD. Participants were recruited using a combination of purposive and snowball sampling techniques. These were supplemented with interviews with two staff of disability rehabilitation centers in Belu to understand any additional barriers. Data analysis was guided by a qualitative data analysis framework. Our analysis identified that lack of affordability of healthcare services (high costs and low financial capacity of mothers) was the key barrier for access to healthcare and rehabilitation services CWD. Religious or faith-based factors, such as being a non-Catholic (Belu is predominantly Catholic), converting from Catholic to other religions, and the belief in children’s disability condition as “God’s will”, were also influencing factors for lack of access to the services. Shortage of staff, distrust in the therapy skills of staff at rehabilitation centers, and unavailability of appropriately trained healthcare professionals were structural or system-related barriers. The findings indicate the need for government-owned and run disability rehabilitation centers (not faith-based), the provision of fully subsidised health insurance to provide free services, and the provision of qualified therapists and healthcare professionals (to build trust) in Belu and other similar settings in Indonesia.